Penerapan Manajemen Personalia di Madrasah Tsanawiyah Pondok Pesantren Qodratullah - Aditya Novali (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 1970)
This study aims to determine how the management of education by implementing personnel management in the Madrasah Tsanawiyah Islamic Boarding School Qodratullah Langkan Banyuasin III District, Banyuasin Regency. The type of research used is field research using a qualitative approach. The data used are of two kinds namely primary data sources and secondary data. Data collection techniques using observation, documentation and interviews. The collected data were analyzed using qualitative data analysis. The findings of this study are that the application of education management has been carried out quite well, in accordance with the conditions of the Islamic Boarding School Qodratullah Islamic Boarding School. This means that all of the management applications have been carried out but due to limited supporting factors in the form of infrastructure and the state of school personnel, the application of management is carried out to the extent of existing management. From the results of this study also showed that the concept of acceptance of professional educators, proper placement of personnel, and unfavorable personnel welfare must always be considered, because it is very influential in the development of the Qodratullah Islamic Boarding School in Banyuasin, South Sumatra. This concept needs to be empowered and developed especially in improving the management of learning in the Qodratullah Islamic Boarding School.